Hukum, Politik dan Westernisasi - Muhazir Muhazir (Politica: Jurnal Hukum Tata Negara dan Politik Islam, 2022)
It is undeniable that in the traditionalist group which is motivated by the belief that the time of the Apostle and the Companions was ideal, the term ideal is sometimes defined as the best of the best period. Behind the triumph of the Ottoman Turks in its leadership, there were various problems caused by expansion efforts. This paper reviews the dynamics that occurred during the Ottoman Turkish dynasty and the effects of its leadership style. This paper is a literature review by reviewing various writings and research, historical approach in this paper is used to theoretically describe historical construction during the Ottoman Turkish dynasty. This paper argues that the contribution of the ideal system of government cannot be separated from the role of the Abbasid government. The Ottoman and Abbasid dynasties were kingdoms that had put reforms in creating a government, economic, legal, and political system.